PENGARUH SUMBER DAYA MANUSIA DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA: ( STUDI KASUS KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO) - Suiton, Andini; Mattoasi, Mattoasi; Usman, Usman (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The management of village funds involves not only distributing and using government resources but also demands accountability and transparency from village administrations. Accountability thus becomes a key determinant of public trust in the integrity and performance of local governance. This research aims to analyze the influence of human resources and the clarity of budget targets on the accountability of village fund management in Kabila Bone District, Bone Bolango Regency. Methods: A descriptive quantitative method was employed with purposive sampling, involving 54 respondents. Data were analyzed using descriptive statistics, data quality tests, classical assumption tests, multiple regression, and hypothesis testing.Results: Human resources have a positive and significant impact on accountability in village fund management, whereas budget target clarity does not significantly affect it. The study concludes that enhancing village officials' competence through ongoing training in accounting, regulatory compliance, and financial reporting systems is crucial to improving accountability in managing village funds. Future research should expand the model by incorporating additional variables to further explain the determinants of accountability in public financial management. Keywords: Accountability, Budget Target Clarity, Human Resources, Village Fund Management